New fully bio-based PLLA triblock copoly(ester urethane)s as potential candidates for soft tissue engineering. (October 2016) - Fabbri, M.; Soccio, M.; Costa, M.; Lotti, N.; Gazzano, M.; Siracusa, V.; Gamberini, R.; Rimini, B.; Munari, A.; García-Fernández, L.; Vázquez-Lasa, B.; San Román, J.
Abstract: Novel fully bio-based poly(lactic acid) copoly(ester-urethane)s have been successfully synthesized. The new system is composed of a series of A-B-A triblock copolymers, where A, hard block, is poly(lactic acid) and B, soft block, is an ad hoc designed random aliphatic copolyester, poly(butylene succinate/azelate), characterized by high flexibility. Triblock units are joined by hexamethylene diisocyanate, known chain extender that allows the obtaining of polymers with high molecular weights. The samples synthesized were subjected to a detailed molecular, thermal, structural and mechanical characterization. The results obtained, show that copolymerization leads to better mechanical response with respect to poly(lactic) acid homopolymer. Moreover, the presence of the soft block in the main polymer chain facilitates the process of biodegradability. Nanoparticles of selected copolymers fabricated by using the nanoprecipitation method showed rounded morphology and average hydrodynamic diameters around 180 nm. Cellular behavior was assessed using human fibroblasts in vitro assays and results showed absence of cytotoxicity and a good cellular adhesion and proliferation on all the copolymer surfaces.